The Equivalence of Translated Songs Lyrics and their Effects - The Case of Translated Ecclesial Songs - Suharto, S.; Subroto, Edi (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2014)
This study aimed at describing the equivalence of eclessial song lyrics, which belong to the content word, the meaning of the sentences and their effect on church songs. The method used in this study is descriptive and qualitative by using music, language, and interdiciline approach. The data collection method used questionnaires technique, interview, documents and content analysis. The data used are 5 documents of songs chosen purposively as the primary data. Based on the data being analyzed, the results of this study were: 1) The translated content word located in the same bars and equivalent was around 27.07%, the translated content word located in the same bars, but not equivalent was 18.34%, the translated content word located in the different bars, but equivalent was 11.79%, the translated content word located in the different bars and not equivalent was 2.62%, and the untranslated words were 4.17%. 2) The translation of equivalence beautiful lyrics showed the beauty of the song was equivalent at 17.02%, the beauty of the song was less equivalent at 29.78%, the beauty of the song was not equivalent of 61.70%. 3). The differences of structure caused the incorrect dictions or choice of words and missing words in the translated lyrics.